PLANEJAMENTO FAMILIAR: UM NOVO OLHAR ACERCA DA FORMAÇÃO DA PROLE E GARANTIA DA FORMAÇÃO DE PERSONALIDADE CONDIZENTE COM O CONVÍVIO EM SOCIEDADE (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
Family planning is indicative of responsible parenthood. The disorderly growth of the population, without effective family planning, leads to population poverty. The first chapter presents an introduction to the topic of family planning. The second brings some concepts of family planning. The third chapter addresses family planning in some countries of the world. The fourth chapter shows the vision of the Vatican. The fifth chapter addresses family planning in Brazil. The sixth chapter brings the constitutional view on the subject. It is concluded that family planning can provide a worthy formation of the personality, but unfortunately it is still effective in underdeveloped countries.